How cash transfers enable agency through livelihoods in South Africa. (July 2020) - Nnaeme, Chibuikem C.; Patel, Leila; Plagerson, Sophie
Highlights: The study provides the linkages between agency, cash transfers and livelihoods. South Africa's cash transfers enable beneficiaries to enact 'developmental agency'. Cash transfers served as catalysts for participants' livelihood decision-making. The grants were used by participants as seed funding to start and grow livelihoods. The agency established counters the view that beneficiaries are passive dependent. Abstract: Although cash transfers primarily support recipients' consumption of goods for basic needs, there is a growing body of evidence showing that they can also promote livelihood activities. Yet there has been little theoretical or empirical analysis of the contribution of human agency in facilitating the conversion of cash transfers into livelihood strategies. This paper presents findings from a qualitative study conducted in a poor urban community in South Africa. Giddens's structuration theory provides an analytical tool to understand how cash transfers enable agency through livelihood activities. The first finding is that beneficiaries conceptualized as "developmental agents", were highly motivated to improve their lives; and that they were decision-makers who made different types of strategic and operational decisions to improve their livelihood activities. Agency expressed through a strong sense of self, ingenuity and resilience denoted participants as active rather than passive recipients of public assistance. Receipt of cash transfers activated agency, enabling recipients to start or diversify livelihood activities. Second, the challenges and constraints are identified that limited their livelihood outcomes, such as high levels of poverty in the community and unemployment. Finally, it shows how beneficiaries attempted to circumvent structural barriers to human development. The study contributes to understanding the interaction between citizens and the state in reducing poverty and in promoting social and economic development.